A copper-based catalyst, preparation method and application thereof
By doping zirconium silicate into the Cu/SiO2 catalyst and introducing auxiliary metals, a copper-based catalyst with excellent performance was prepared, which solved the problems of catalyst stability and short service life, and achieved efficient indole synthesis.
Patent Information
- Application Number
- CN202411676394.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Cu/SiO2 catalyst has poor stability and short service life during the synthesis of indole, making it difficult to achieve industrial application.
Silica doped with zirconium silicate is used as a support, and a copper-based catalyst composed of metals such as copper, zinc, yttrium and cerium is prepared by ball milling and impregnation precipitation to improve the stability and activity of the catalyst.
The stability and service life of the catalyst were significantly improved. The indole yield reached more than 60% during the 10-hour reaction, the yield remained above 40% during the 200-hour reaction, and the yield remained above 32% during the 500-hour reaction.
Smart Images

Figure CN119175101B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of indole synthesis, and in particular to a copper-based catalyst, a preparation method and application thereof. Background Art
[0002] With the rapid development of the hydrogen energy industry, organic liquid hydrogen storage is poised to rapidly emerge as a key technology for hydrogen storage and transportation solutions. Market demand for indole compounds, the primary nitrogen heterocyclic carrier for hydrogen storage, is expected to increase significantly. However, current methods for synthesizing indole, such as separation and extraction, the o-toluidine method, and the Fischer method, all suffer from complex processes, high energy consumption, and high costs, which clearly hinders the large-scale application of organic liquids.
[0003] The alcoholamine method, a one-step synthesis of indole from aniline and ethylene glycol, effectively addresses cost issues. However, this technical route hinges on catalyst development. Numerous such catalysts have been reported in relevant literature and patents, but their primary drawbacks are the high cost and complex structure of precious metal catalysts. Furthermore, these catalysts suffer from high reaction temperatures, severe catalyst deactivation, limited yield and selectivity advantages, and difficulties in achieving continuous operation. Consequently, these catalysts have yet to achieve industrial application. Currently, the mainstream research focus on Cu / SiO2 catalysts for the synthesis of indole using the alcoholamine method is on high-yield, good selectivity, and low-byproduct catalysts, using SiO2 as a support. However, these catalysts currently suffer from short lifespans and poor stability.
[0004] Therefore, in the field of indole synthesis technology, the poor stability and short service life of Cu / SiO2 catalysts have become technical problems that need to be solved urgently. Summary of the Invention
[0005] To solve the above problems, in a first aspect, the present invention provides a copper-based catalyst, which comprises a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass;
[0006] The carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0-20% of the mass of the silica carrier; the active component is copper; the auxiliary metal is composed of a first auxiliary metal and a second auxiliary metal in a mass ratio of 2-10:1-5, the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.
[0007] Preferably, the doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier.
[0008] Preferably, the first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.
[0009] Preferably, the support is a silica support.
[0010] In a second aspect, the present invention provides a method for preparing the copper-based catalyst described in the first aspect, the preparation method comprising:
[0011] S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min to 200 r / min for 6 h to 18 h to obtain a carrier; wherein the zirconium silicate accounts for 0 to 20% of the mass of the silicon dioxide;
[0012] S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the support and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing to stir for 2 h to 4 h, adjusting the pH value to 9 to 11, aging for 12 h to 24 h, and washing until the pH value of the supernatant is within the range of 7 to 8 to obtain a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal;
[0013] S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.
[0014] Preferably, the pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of the silica is 200 m 2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 um.
[0015] Preferably, the mixed salt solution is a nitrate, chloride or acetate solution;
[0016] The first auxiliary agent is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary agent is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.
[0017] Preferably, in S3, the drying temperature is 60°C to 100°C, and the drying time is 24 h; the calcination temperature is 400°C to 700°C, and the calcination time is 2 h to 8 h, and the calcination heating rate is 2°C·min -1~8 ℃·min -1 .
[0018] In a third aspect, the present invention provides an application of the copper-based catalyst described in the first aspect, wherein the copper-based catalyst is used in a reaction of synthesizing indole compounds or indole derivatives by an alcoholamine method.
[0019] Preferably, the application includes:
[0020] The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere of hydrogen to nitrogen with a volume ratio of 1:4;
[0021] Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h -1 ~3.0 h -1 The reaction is carried out under the conditions of , to obtain an indole compound or indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.
[0022] When the raw materials are N-methylaniline and ethylene glycol, N-methylindole can be obtained by directly utilizing the copper-based catalyst and process conditions; when the raw materials are N-ethylaniline and ethylene glycol, N-ethylindole can be obtained by directly utilizing the copper-based catalyst and process conditions; when the raw materials are m-methylaniline and ethylene glycol, 4-methylindole and 6-methylindole can be obtained by directly utilizing the copper-based catalyst and process conditions; when the raw materials are p-methylaniline and ethylene glycol, 5-methylindole can be obtained by directly utilizing the copper-based catalyst and process conditions; when the raw materials are aniline and glycerol, 3-methylindole can be obtained by directly utilizing the copper-based catalyst and process conditions; and when the raw materials are aniline and 1,2-propylene glycol, 2-methylindole can be obtained by directly utilizing the copper-based catalyst and process conditions.
[0023] Preferably, when the raw materials are aniline and propylene glycol, the molar ratio of aniline to ethylene glycol is 9:1, the copper-based catalyst is directly used, and the reaction temperature is 260 ° C and the space velocity is 3.0 h -1 The reaction was carried out under the conditions of , and a yield of 76.4% of 3-methylindole (based on glycerol) was obtained.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention provides a copper-based catalyst, a preparation method and an application thereof, and relates to the technical field of indole synthesis. The copper-based catalyst consists of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass. The carrier is a silica carrier doped with zirconium silicate, and the doping amount of zirconium silicate is 0% to 20% of the silica carrier mass. The active component is copper. The promoter metal consists of a first promoter metal and a second promoter metal in a mass ratio of 2 to 10:1 to 5. The first promoter metal is one or more of zinc, magnesium, calcium, cobalt and nickel, and the second promoter metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum and tungsten. The copper-based catalyst provided in the embodiment of the present invention has excellent performance and has significant advantages in terms of sustained reaction life. When preparing indole, the copper-based catalyst can react continuously for 10 hours with a yield of more than 60%, the yield remains above 40% for 200 hours, and the yield remains above 32% for 500 hours.
[0026] The copper-based catalyst provided in the embodiment of the present invention, on the one hand, introduces zirconium in a more stable and warmer manner, that is, by doping zirconium silicate into the silica carrier, which not only does not reduce the activity of the Cu / SiO2 catalyst, but on the contrary greatly improves the stability of the catalyst. The silica carrier doped with zirconium silicate can improve the stability of the Cu / SiO2 catalyst. The more stable it is, the higher its catalytic activity and the longer its life. On the other hand, the introduction of the first and second additive metals not only jointly enhances the interaction between the active copper component and the support, but also jointly increases the dispersion of the active copper component, both of which are beneficial to improving the anti-sintering ability of the active copper component, thereby enhancing the stability of the catalyst. Specifically, the introduction of the first additive metal and the active copper component to form an alloy not only disperses the distance between the active copper components, thereby improving the dispersion of the active copper component on the surface of the silica support, preventing the catalytic activity reduction caused by aggregation during the indole synthesis reaction, and more fully contacting the reaction system during the indole synthesis reaction, thereby improving the stability and service life of the copper-based catalyst. It also strengthens the interaction between the active copper component and the support, thereby inhibiting the sintering and agglomeration of the active copper component during the indole synthesis reaction and reducing the carbon deposition of the catalyst. The introduction of the second additive metal not only affects the electron transfer, lattice distortion, and grain size of the active copper component, but also affects the acidity and alkalinity of the support surface and the surface structure, thereby improving the activity and stability of the copper-based catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0028] Figure 1 This is a flow chart of a method for preparing a copper-based catalyst according to an embodiment of the present invention;
[0029] Figure 2 This is a scanning electron microscope image of the copper-based catalyst prepared in Example 2 of the present invention;
[0030] Figure 3 This is the pore size distribution diagram of the copper-based catalyst prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.
[0032] Where specific experimental steps or conditions are not specified in the examples, the conventional experimental steps or conditions described in the prior art in the art may be used. The reagents and other instruments used, for which the manufacturer is not specified, are all conventional reagent products that can be obtained commercially. Furthermore, the accompanying drawings are merely schematic illustrations of the embodiments of the present disclosure and are not necessarily drawn to scale. Identical reference numerals in the figures represent identical or similar parts, and their repeated descriptions will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0033] To extend the service life of the Cu / SiO2 catalyst, the inventors replaced the active component of the catalyst with ZrO2, resulting in a ZrO2 / SiO2 catalyst. Specifically, zirconium nitrate was first loaded onto a SiO2 carrier, followed by drying and calcination to obtain the ZrO2 / SiO2 catalyst. However, compared to the Cu / SiO2 catalyst, the ZrO2 / SiO2 catalyst had a lower yield and produced more byproducts. To extend the service life of the Cu / SiO2 catalyst, the inventors introduced zirconium as an additive into the Cu / SiO2 catalyst. However, they found that the additive zirconium did not synergize with the main catalyst Cu to increase the service life or stability of the catalyst, and instead significantly reduced the catalytic activity of the Cu / SiO2 catalyst. Therefore, achieving a catalyst with both high catalytic activity and long service life is extremely difficult.
[0034] In view of this, the present invention changes the method of introducing zirconium to doping zirconium in the carrier and doping in the form of zirconium silicate. Not only does it not reduce the activity of the Cu / SiO2 catalyst, but the stability of the catalyst is greatly improved. Furthermore, in order to improve the catalytic activity and life of the Cu / SiO2 catalyst doped with zirconium silicate in the SiO2 carrier, two different auxiliary metals are introduced at the same time. On the one hand, the interaction between the active component copper and the carrier is enhanced, and on the other hand, the dispersion degree of the active component copper is increased. Both aspects are beneficial to improving the anti-sintering ability of the active component copper and enhancing the stability of the catalyst.
[0035] In the first aspect, the present invention provides a copper-based catalyst, which is composed of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the mass of the carrier, and the promoter metal accounts for 3% to 15% of the mass of the carrier; wherein the carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0 to 20% of the mass of the silica carrier; the active component is copper; the promoter metal is composed of a first promoter metal and a second promoter metal in a mass ratio of 2 to 10:1 to 5, wherein the first promoter metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second promoter metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.
[0036] The copper-based catalyst provided in the embodiment of the present invention, on the one hand, introduces zirconium in a more stable and warmer manner, that is, by doping zirconium silicate into the silica carrier, which not only does not reduce the activity of the Cu / SiO2 catalyst, but on the contrary greatly improves the stability of the catalyst. The silica carrier doped with zirconium silicate can improve the stability of the Cu / SiO2 catalyst; on the other hand, the introduced first auxiliary metal and second auxiliary metal not only jointly enhance the interaction force between the active component copper and the carrier, but also jointly increase the dispersion degree of the active component copper. Both aspects are beneficial to improving the anti-sintering ability of the active component copper, thereby enhancing the stability of the catalyst. The more stable it is, the higher its catalytic activity and the longer its life.
[0037] Specifically, the first additive metal forms an alloy with the active copper component. This, on the one hand, disperses the distance between the active copper components, thereby improving the dispersion of the active copper component on the silica support surface. This prevents the reduction of catalytic activity caused by aggregation during the indole synthesis reaction. The copper-based catalyst is more fully exposed to the reaction components during the indole synthesis reaction, thereby improving the stability and service life of the copper-based catalyst. Furthermore, it also strengthens the interaction between the active copper component and the support, thereby inhibiting sintering and agglomeration of the active copper component during the indole synthesis reaction and reducing carbon deposition on the catalyst. The introduction of the second additive metal not only affects the electron transfer, lattice distortion, and grain size of the active copper component, but also affects the acidity and alkalinity and surface structure of the support surface, thereby improving the activity and stability of the copper-based catalyst.
[0038] The copper-based catalyst provided in the embodiments of the present invention has excellent performance and has significant advantages in terms of sustained reaction life. When preparing indole, the copper-based catalyst can react continuously for 10 hours with a yield of more than 60%, the yield remains above 40% after 200 hours of reaction, and the yield remains above 32% after 500 hours of reaction.
[0039] In addition, since the raw materials of the copper-based catalyst provided by the embodiment of the present invention do not contain precious metals, its main components copper and silicon dioxide are inexpensive and are common chemical raw materials, and have the characteristics of low cost and large-scale production and application.
[0040] In some embodiments of the present invention, the doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier.
[0041] In some embodiments of the present invention, the first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.
[0042] The copper-based catalyst provided in this embodiment has a more significant advantage in terms of sustained reaction life. The yield is as high as 64.1% after a continuous reaction of 10 h, the yield is maintained at 55.5% after a reaction of 200 h, and the yield is maintained at above 38.9% after a reaction of 500 h.
[0043] In some embodiments of the present invention, the support is a silica support.
[0044] In a second aspect, the present invention provides a method for preparing the copper-based catalyst described in the first aspect, the preparation method comprising:
[0045] S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min to 200 r / min for 6 h to 18 h to obtain a carrier; wherein the zirconium silicate accounts for 0 to 20% of the mass of the silicon dioxide;
[0046] S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the support and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing to stir for 2 h to 4 h, adjusting the pH value to 9 to 11, aging for 12 h to 24 h, and washing until the pH value of the supernatant is within the range of 7 to 8 to obtain a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal;
[0047] S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.
[0048] Specifically, in S2, the preparation process of the copper nitrate solution is as follows: weigh a certain amount of copper nitrate trihydrate Cu(NO3)2·3H2O, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain the copper nitrate solution; in S2, the preparation process of the auxiliary metal impregnation solution is as follows: weigh a certain amount of the first auxiliary metal and the second auxiliary metal, add them to 100 mL of deionized water and stir until they are completely dissolved to obtain the auxiliary metal impregnation solution; in S2, the pH value thereof is adjusted to 9~11 using one or more of a Na2CO3 solution, a NaOH solution, and an NH3·H2O solution as a regulator; in S3, the dried solid is ground until there is no granularity, then loaded into a porcelain boat, and then placed in a muffle furnace for roasting.
[0049] The present invention utilizes the simplest impregnation precipitation method to achieve doping of the support and the introduction of the first and second promoter metals. The resulting copper-based catalyst exhibits excellent performance, with overall performance comparable to that of industrial production applications, while also being low-cost and suitable for large-scale production. Furthermore, due to the simplicity of the process and the proven, reliable process, the resulting product yields minimal variability between batches and stable performance.
[0050] Specifically, zirconium silicate is first doped into a silica carrier by dry ball milling; the obtained carrier is then contacted with a promoter metal impregnation solution and a copper nitrate solution, so that the active component copper, the first promoter metal and the second promoter metal are adsorbed on the carrier; finally, the copper-based catalyst is obtained through drying and calcination.
[0051] In some embodiments of the present invention, the pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of the silica is 200 m2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 um.
[0052] In some embodiments of the present invention, the mixed salt solution is a nitrate, chloride or acetate solution; the first auxiliary agent is one or more of zinc, magnesium, calcium, cobalt, and nickel; and the second auxiliary agent is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.
[0053] In some embodiments of the present invention, in S3, the drying temperature is 60°C to 100°C, and the drying time is 24 hours; the calcination temperature is 400°C to 700°C, and the calcination time is 2 hours to 8 hours, and the calcination heating rate is 2°C·min -1 ~8 ℃·min -1 .
[0054] Furthermore, the drying temperature was 80 °C, the calcination temperature was 600 °C, the calcination time was 8 h, and the calcination heating rate was 5 °C·min -1 .
[0055] In a third aspect, the present invention provides an application of the copper-based catalyst described in the first aspect, wherein the copper-based catalyst is used in a reaction of synthesizing indole compounds or indole derivatives by an alcoholamine method.
[0056] The principle of synthesizing indole based on the alcoholamine method is different from that of synthesizing indole by other methods. Therefore, the catalytic effect of the copper-based catalyst provided by the present invention is only for the synthesis of indole from aniline and ethylene glycol. The copper-based catalyst is used in the synthesis of indole compounds, such as indole, 3-methylindole, N-methylindole, etc., and can also be used in the preparation of indole derivatives.
[0057] When the copper-based catalyst provided in the embodiments of the present invention is used for the synthesis of indole by the alcoholamine process, it has a long continuous reaction life. The copper-based catalyst has a yield of more than 60% after a continuous reaction of 10 hours, a yield of more than 40% after a reaction of 200 hours, and a yield of more than 32% after a reaction of 500 hours, showing good industrial application prospects.
[0058] In some embodiments of the present invention, the application includes:
[0059] The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere of hydrogen to nitrogen with a volume ratio of 1:4;
[0060] Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h-1 ~3.0 h -1 The reaction is carried out under the conditions of , to obtain an indole compound or indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.
[0061] Specifically, the reduction is to reduce the copper in the copper-based catalyst to elemental copper to release the elemental copper, which serves as an active site. Thus, during the reaction of aniline and ethylene glycol, the elemental copper can well promote the reaction. When the copper-based catalyst is reduced, the reduction is completed until there is no obvious water vapor in the outlet gas, thereby completing the activation of the copper-based catalyst.
[0062] In this embodiment, since the first promoter metal and the second promoter metal are introduced into the copper-based catalyst, even if all the elemental copper is released before synthesizing indole, the elemental copper will not agglomerate or sinter during the reduction process, and the catalytic activity of the copper-based catalyst will not be affected after the reduction is completed.
[0063] In order to enable those skilled in the art to better understand the present invention, the preparation method provided by the present invention is described below through multiple specific examples.
[0064] Comparative Example 1
[0065] Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at a speed of 100 r / min for 10 h. Then, remove the silica carrier and sieve it for later use.
[0066] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until it is completely dissolved to obtain a copper nitrate solution. Add the copper nitrate solution dropwise to the obtained silica support, stir for 2 h, then add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11. Aged for 12 h, and washed until the pH of the supernatant is in the range of 7-8 to obtain a solid.
[0067] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C min. -1 , to obtain a powdered catalyst.
[0068] 3 g of the catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150°C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature reached 300°C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h / min.-1 ,Evaluation conditions and results are shown in Table 1.
[0069] Comparative Example 2
[0070] Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at a speed of 100 r / min for 10 h. Then, remove the silica carrier and sieve it for later use.
[0071] Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O and add it to 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 11.74 g of zirconium nitrate pentahydrate Zr(NO3)4·5H2O, an auxiliary metal, and add it to 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary agent impregnation solution; add the copper nitrate solution dropwise to the obtained silica support, stir for 3 h, then add the auxiliary agent impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0072] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered catalyst.
[0073] 3 g of the catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150°C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature reached 300°C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h / min. -1 ,Evaluation conditions and results are shown in Table 1.
[0074] It can be seen from Table 1 that after zirconium is introduced into the Cu / SiO2 catalyst in the form of an additive, the additive zirconium cannot synergistically act with the main catalyst Cu to improve the service life or stability of the catalyst, but instead significantly reduces the catalytic activity of the Cu / SiO2 catalyst.
[0075] Example 1
[0076] Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Then, remove the carrier and sieve it for later use.
[0077] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0078] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C min. -1 , to obtain a powdered copper-based catalyst.
[0079] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0080] Example 2
[0081] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0082] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0083] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C min. -1 , to obtain a powdered copper-based catalyst.
[0084] The copper-based catalyst of this embodiment was tested and characterized. Figure 2 and Figure 3 As shown, Figure 2 This is a scanning electron microscope image of the copper-based catalyst prepared in Example 1 of the present invention; Figure 3 This is the pore size distribution diagram of the copper-based catalyst prepared in Example 1 of the present invention.
[0085] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0086] Example 3
[0087] Weigh 40 g of silica and 10 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0088] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0089] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C min. -1 , to obtain a powdered copper-based catalyst.
[0090] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0091] Example 4
[0092] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0093] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 2.28 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 5.33 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 1.08 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 0.78 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first and second auxiliary metals to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8, to obtain a solid.
[0094] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0095] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0096] Example 5
[0097] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0098] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution. Weigh 11.42 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 26.67 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 5.38 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.88 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first and second auxiliary metals to 100 mL of deionized water, and stir until completely dissolved, to obtain an auxiliary metal impregnation solution. Add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8, to obtain a solid.
[0099] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C min. -1 , to obtain a powdered copper-based catalyst.
[0100] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0101] Example 6
[0102] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0103] Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of the first auxiliary metal calcium nitrate tetrahydrate Ca(NO3)2·4H2O, weigh 4.67 g of the second auxiliary metal lanthanum nitrate hexahydrate La(NO3)3·6H2O, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0104] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0105] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0106] Example 7
[0107] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0108] Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of the first auxiliary metal calcium nitrate tetrahydrate Ca(NO3)2·4H2O, weigh 11.54 g of the second auxiliary metal chromium nitrate nonahydrate Cr(NO3)3·9H2O, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0109] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0110] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0111] Example 8
[0112] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0113] Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of calcium nitrate tetrahydrate Ca(NO3)2·4H2O as the first auxiliary metal, weigh 20.83 g of aluminum nitrate nonahydrate Al(NO3)3·9H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0114] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0115] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0116] Example 9
[0117] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0118] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 12.33 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 7.4 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O), weigh 3.12 g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 3.85 g of chromium nitrate nonahydrate (Cr(NO3)3·9H2O), and add the weighed first and second auxiliary metals to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0119] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0120] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0121] Example 10
[0122] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0123] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 7.4 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 12.33 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O), weigh 1.56 g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 13.89 g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O), and add the weighed first and second auxiliary metals to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0124] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0125] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0126] Example 11
[0127] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0128] Weigh 9.45 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water, stirring until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0129] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0130] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0131] Example 12
[0132] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0133] Weigh 28.36 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0134] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0135] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 300 °C, the raw materials were added to the reactor for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0136] Example 13
[0137] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0138] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0139] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0140] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed until no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 280 °C, the raw materials were added for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0141] Example 14
[0142] Weigh 45 g of silica and 5 g of zirconium silicate into a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls and mill at 100 r / min for 10 h. Remove the carrier and sieve it for later use.
[0143] Weigh 18.91 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and add it to 100 mL of deionized water, stirring until completely dissolved, to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 16 g of magnesium nitrate hexahydrate (Mg(NO3)2·6H2O) as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 1.55 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until completely dissolved, to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained support, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate (Na2CO3) solution to adjust the pH to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.
[0144] The solid was placed in a glass watch glass and dried in a vacuum drying oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h with a heating rate of 5 °C·min -1 , to obtain a powdered copper-based catalyst.
[0145] 3 g of copper-based catalyst was loaded into the reactor for reduction. The volume ratio of hydrogen to nitrogen was 1:4 and the reduction temperature was 150 °C. The reduction was completed when no significant water vapor was present in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to produce indole. When the temperature was raised to 350 °C, the raw materials were added for reaction. The molar ratio of ethylene glycol to aniline was 1:7 and the space velocity was 0.5 h -1 ,Evaluation conditions and results are shown in Table 1.
[0146] Table 1 Comparative Examples and Test Results
[0147]
[0148] Thus, Example 1 utilizes a single first and second promoter metal to modify the catalyst. While the improved catalyst stability is improved, specifically, the 200-hour yield increases from approximately 10% to approximately 49%, and the 500-hour yield increases from less than 5% to approximately 22%. Example 2, based on Example 1, further incorporates an appropriate amount of zirconium silicate into the support. The test results in Table 1 show that the copper-based catalyst of Example 1 decreases in activity as the indole synthesis reaction time increases. The copper-based catalyst obtained in Example 2 exhibits significant improvements in stability, specifically, the 200-hour yield increases from approximately 10% to approximately 55%, and the 500-hour yield increases from less than 5% to approximately 39%. Example 2 exhibits the longest lifespan of all the examples. Similar effects are observed in the catalysts of Examples 3 through 14, with significant improvements in stability.
[0149] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification.
[0150] For simplicity of description, the method embodiments are described as a series of actions. However, those skilled in the art should be aware that the present invention is not limited by the order of the actions described, as certain steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also be aware that the embodiments described in this specification are preferred embodiments, and the actions and components involved are not necessarily required for the present invention.
[0151] The above is a detailed introduction to a copper-based catalyst, preparation method and application provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core concept. At the same time, for those skilled in the art, according to the concept of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the contents of this specification should not be understood as limiting the present invention.
Claims
1. A copper-based catalyst, characterized in that The copper-based catalyst is composed of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass; The carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier; the active component is copper; the auxiliary metal is a first auxiliary metal and a second auxiliary metal in a mass ratio of 2-10:1-5, the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.
2. The copper-based catalyst according to claim 1, characterized in that The first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.
3. A method for preparing a copper-based catalyst according to any one of claims 1 to 2, characterized in that: The preparation method comprises: S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min-200 r / min for 6 h-18 h to obtain a carrier; wherein the zirconium silicate is 1-20% of the mass of the silicon dioxide; S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the carrier and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing stirring for 2 h to 4 h, adjusting the pH value to 9 to 11 and aging for 12 h to 24 h, washing until the pH value of the supernatant is within the range of 7 to 8, and obtaining a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal; S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.
4. The preparation method according to claim 3, characterized in that: The pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of the silica is 200 m 2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 µm.
5. The preparation method according to claim 3, characterized in that: The mixed salt solution is a nitrate, chloride or acetate solution.
6. The preparation method according to claim 3, characterized in that: In S3, the drying temperature is 60°C to 100°C, and the drying time is 24 h; the roasting temperature is 400°C to 700°C, and the roasting time is 2 h to 8 h, and the roasting heating rate is 2°C·min -1 ~8 ℃·min -1 .
7. Use of the copper-based catalyst according to any one of claims 1 to 2, characterized in that: The copper-based catalyst is used in the reaction of synthesizing indole compounds or indole derivatives by alcoholamine method.
8. The use according to claim 7, characterized in that: The applications include: The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere with a hydrogen to nitrogen volume ratio of 1:4; Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.